FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PEKERJA BATU BATA DI DESA TALANG BELIDO TAHUN 2021 - Tito Nurfajri; Subakir Subakir; Abul Ainin Hapis (Sekolah Tinggi Pariwisata Mataram, 2022)
Complaints of low back pain is one of the complaints that can reduce work productivity. Bricks workers are one of the workers who are at risk for low back pain. The purpose of this study was to determine the factors associated with complaints of low back pain among brick workers in Talang Belido Village. This study used a cross sectional design. The research sample was male brick workers in Talang Belido Village as many as 38 people. Sampling using total sampling technique. This research was conducted in August 2021 in Talang Belido Village. The research instrument is a questionnaire. Data were analyzed by univariate and bivariate using chi square test. As many as 55.3% of respondents experienced complaints of low back pain, 31.6% of respondents worked with risky manual handling, 55.3% of respondents had a moderate workload and 42.1% of respondents had a very high risk work attitude. There is a relationship between manual handling (p = 0.007), workload (p = 0.000) and work attitude (p = 0.020) with complaints of lower back pain among brick workers in Talang Belido Village, Muaro Jambi Regency in 2021. with ergonomic principles. Posture when working in a balanced state in order to work comfortably and for a long time.